DEMOGRAPHICAL DIFFERENCES AMONG MALAYSIA PERSPECTIVE ON FAKE NEWS DURING COVID-19 ENDEMIC - Wan Hashridz Rizal bin Wan Abu Bakar,; Abdul Rauf Ridzuan,; Fahmi Zaidi Bin Abd Razak, (Journal of Islamic, Social, Economics and Development, 2023)
Fake news is sensational information that is circulated under the guise of accurate news in an effort to mislead those who will believe it. Fake news has drawn a lot of attention due to its quick spread on social media and the threat it presents to society by influencing the public's opinion. It is crucial to comprehend the nature and characteristics of the COVID-19 infodemic in the midst of the massive influx of fake news. This study seeks to determine how Malaysian perspectives on fake news differ in terms of demographics. This study concentrated on gender, age, and level of education. Based on the multistage cluster sampling method, this quantitative study was conducted in a number of picked states, and the data collected came from as many as 277 respondents. Based on descriptive statistics, the research's findings demonstrate that women made up 63.8 percent of the study's respondents. 65.9% of the respondents to this research, or the majority, are aged between 18 and 27. Those with a diploma or a bachelor's degree make up the majority of respondents (64.9%) in terms of educational level.